HOW TO IMPROVE VOCABULARY THROUGH DIFFERENT STRATEGIES - Umaralieva, Munojat Mashrabovna; Yakhyoyeva , Sarvinoz Khayotjon kizi (Educational Research in Universal Sciences, 2023)
Learning vocabulary is an essential component of studying English. Prior to mastering the four language skills (reading, writing, listening, and speaking), students must acquire a solid foundation of vocabulary to support their English learning. English vocabulary plays a crucial role in the language development of young learners studying a foreign language. It is important for teachers to be creative in selecting learning materials and stimulate students’ interest in English, particularly when it comes to vocabulary. Strategies must be employed by teachers to enhance the teaching and learning process. The teaching approach for young learners differs from that for adults, as children tend to be more enthusiastic, active, and adaptable. This research study is classified as descriptive qualitative research.